2020
DOI: 10.1016/j.ajpath.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid-Related Orphan Receptor RORγt in CD4+ T-Cell–Mediated Intestinal Homeostasis and Inflammation

Abstract: Retinoic aciderelated orphan receptor (ROR)-gt, the master transcription factor of the Th17 subset of CD4 þ Th cells, is a promising target for treating a host of autoimmune diseases. RORgt plays a vital role in the pathogenesis of inflammatory bowel diseasesdCrohn disease and ulcerative colitisdcaused by untoward reactivity of the immune system to the components of the intestinal microbiome. The mammalian intestinal tract is a highly complex and compartmentalized organ with specialized functions, and is a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 118 publications
(186 reference statements)
0
31
0
Order By: Relevance
“…RORγt mRNA expression was however decreased in T cell transfer colitis mice, but significantly increased upon UAMC-00050 treatment. This latter phenomenon may be due to the fact that nonpathogenic Th17 cells might lose RORγt expression during colitis, converting them into the pathogenic Th1-like Th17 cells as recently proposed ( Mickael et al, 2020 ). Furthermore, RORγt is also present in Treg cells ( Mickael et al, 2020 ), which thereby demonstrates the therapeutic effect of increased RORγt expression levels.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…RORγt mRNA expression was however decreased in T cell transfer colitis mice, but significantly increased upon UAMC-00050 treatment. This latter phenomenon may be due to the fact that nonpathogenic Th17 cells might lose RORγt expression during colitis, converting them into the pathogenic Th1-like Th17 cells as recently proposed ( Mickael et al, 2020 ). Furthermore, RORγt is also present in Treg cells ( Mickael et al, 2020 ), which thereby demonstrates the therapeutic effect of increased RORγt expression levels.…”
Section: Discussionmentioning
confidence: 78%
“…This latter phenomenon may be due to the fact that nonpathogenic Th17 cells might lose RORγt expression during colitis, converting them into the pathogenic Th1-like Th17 cells as recently proposed ( Mickael et al, 2020 ). Furthermore, RORγt is also present in Treg cells ( Mickael et al, 2020 ), which thereby demonstrates the therapeutic effect of increased RORγt expression levels. The above findings suggest a role for Th1, Th17 and Treg cell subsets in the mechanism of action by which UAMC-00050 ameliorates intestinal inflammation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The RORγt+ Tregs subset might be involved in these unanticipated effects. The function of these regulatory cells was thought to be controlled partly by RORγt ( 45 ). Kleinewietfeld et al showed that a low molecular weight RORγt inhibitor could influence the frequencies of regulatory T-cells (Tregs) beside the Th17 response.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, gut-homing Foxp3 Tregs are required for intestinal tolerance in the lamina propria. IL-10 is an important cytokine produced by a large number of Tregs in the gut and helps to inhibit immune responses and maintain immune tolerance (17). Its importance in the intestinal immune milieu is apparent in both mice and humans as IL-10 deficient mice develop spontaneous inflammation of the colon, and humans with mutations in IL-10 or IL-10 receptor (IL-10R) also develop colitis at an early age (18).…”
Section: Introductionmentioning
confidence: 99%